KAJIAN PENCAHAYAAN CAMPURAN DI RUANG BENGKEL KAYU - Isda Wdyani, Sumardjito (Universitas Negeri Yogyakarta, 2015)
ABSTRACTThis study is aimed to discover the strong lighting at carpentry of Engineering Faculty UNYmainly at between 08.00 A.M.-02.00 P.M. Light is an absolute requirement for men to see theirworld. Natural lighting is the light which uses the direct sunlight. Artificial lighting is all forms oflight that comes from a tool created by humans. Mixed lighting is the fusion between naturallight and artificial lighting. The study was begun by studying the basic theory and standardmixed lighting in the carpentry, then do observation, measurement, drawing, determining thepoint of measurement and data collection Data collection was conducted by measurement usingLuxmeter's between at 08:00, 10:00, 12:00 , 02.00 P.M. The data collected in the measurementof as much as 3 times in the same hour. The findings indicate that the average yield stronglighting in the carpentry meet the standard (200 luv) in the amount of 427.13 lux (sunshine),357.00 lux (rainy weather), and 363.12 lux (cloudy weather). It is known from the study that thestrongest lighting in the carpentry when the weather is bright and the weakest lighting is 427.13lux and in wet weather it is 357.00 lux.Keywords: Carpentry, Illumination. Mixed Lighting